An efficient approach to the Klein–Gordon equation: an application of the decomposition method. (13th February 2006) - Inc, M.; Ergut, M.; Evans, D.J.
In this paper, we study a reliable numerical approximation of the linear and non-linear Klein–Gordon equations by using the Adomian's decomposition method. The solution is calculated in the form of a series with easily computable components. We prove the convergence of this method applied to the non-linear Klein–Gordon equation. The numerical results demonstrate the effectiveness of the method for these types of equations.